DIALOGUE ABOUT THE THEOLOGY OF THE SALIB IN THE QUR'AN: An Analytical Study of QS. An-Nisa’ verse 157 - Hayati, Safira Malia; Putra, Afriadi (el-Umdah, 2022)
One of the discourses that has always been a polemic is between divine religions regarding their concept of divinity in terms of their uluhiyyah. Although they are seen as having similarities in monotheism, they have quite paradigmatic differences. This article aims to have a dialogue about the theology of the Salib in the Qur'an Surah An-Nisaa verse 157 which is considered an accusation against the death of Jesus. Meanwhile, the Jews considered the crucifixion as a form of humiliation that Jesus had to experience as a disturbance to society. This attitude of exclusivism is inherent in every religious community. Being moderate is very necessary in this kind of case. This is where broad religious insight is needed to become a moderate person. This diversity in diversity is a challenge as well as a problem that must be solved. This verse is interpreted with the view of Fakhruddin Ar-Razi in his Tafsir al-Kabir interpretation which ultimately concludes that Jesus was raised and saved by Allah. Either the lifting of the soul as well as the body to the sky, or lifting it in the sense of exalting its position and degree, being exalted and glorified.